PERAN SERVICESCAPE DALAM PENYELENGGARAAN SEBUAH EVENT - Theodora Mulyono, Stephanie (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
This research analyzes the role of servicescape in organizing an event. The unit analysis is an event organized by the Travel Industry Management Study Program, School of Hospitality and Tourism, Universitas Pelita Harapan, namely the 8 th Annual National Guiding Competition 2018. The main objective of this research is to see the effect of servicescape on the satisfaction of stakeholders of the guiding competition event. Sampling was done by means of simple random sampling. The data obtained to analyze the independent variable (servicescape) on the dependent variable (satisfaction). The results showed that the servicescape had a significant effect on the satisfaction of the stakeholders of the guiding competition event.